(untitled) (SCIENCE TIME JOURNAL, 2026)
This study compares the Oguz Khagan Epic and the Tain Bo Cuailnge, analyzing their structures and mythologies. Using Propp, Campbell, and Levi-Strauss, it explores patterns of heroism, social organization, and cosmology within distinct oral traditions.